TECTONIC ZONES STUDYING USING INVERSE LINEARLY-NONLINEAR METHODS OF GRAVITY TO SELECT A SITE FOR ECOLOGICALLY RISKY OBJECTS BUILDING - MINENKO, P.; MINENKO, R. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Methods of the decision of return problems gravity which complex use is a necessary condition for effective studying tectonic zones in files of rocks of the crystal base are developed.